The effects of body mass reduction on the anaerobic power and selected somatic characteristics of Greco-Roman wrestlers - Kuzmicki, S.; Kruszewski, A.; Kruszewski, M. (Biomedical Human Kinetics, 2023)
Study aim: The aim of the study was to determine the effects of body weight loss on the levels of somatic features and peak power of senior Greco-Roman wrestlers from the Polish national team.